The Impact of Structure on Oxidatively Generated DNA Damage Products Resulting from the C3′‐Thymidinyl Radical. Issue 2 (28th December 2012) - Amato, Nicholas J.; Bryant‐Friedrich, Amanda C.
<x xml:space="preserve">Abstract</x> What's the damage? Trapping the C3′‐thymidinyl radical in biologically significant architectures delivers both the repaired oligomer and 1‐(2′‐deoxy‐β‐D‐threo‐pentofuranosyl)thymidine‐containing substrates. The stereoselectivity of the reduction was found to be dependent upon the DNA structure.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>